Strategi Pengembangan Agrowisata Buah Naga Palopat Maria di Kota Padangsidimpuan - Tarihoran, Nur Ihsani Afsah; Puddin, Khafi (Masyarakat Ekonomi Syariah Bogor, 2024)
Padangsidimpuan City has reliable agrotourism potential in increasing regional and community income. One of the agrotourism spots in Padangsidimpuan City is Palopat Maria Dragon Fruit Agrotourism. Palopat Maria Dragon Fruit Agrotourism is an agrotourism destination that relies on the natural beauty of plantations and enjoys the authenticity of dragon fruit. The research was conducted in November 2023 at Palopat Maria Dragon Fruit Agrotourism, Padangsidimpuan Hutaimbaru District, Padangsidimpuan City, North Sumatra 22733. This research resulted that Palopat Maria Dragon Fruit Agrotourism shows that the internal and external factors that determine the development of agrotourism are in above average conditions. -average, with a focus on human resources, finance, marketing, production, tourist attractions, as well as facilities and infrastructure.